Perceptual fluctuations within the entrepreneurial journey: Experience from process-based entrepreneurship training - Iuliia Trabskaia; T\~onis Mets (Administrative Sciences, 2021)
The entrepreneurial idea and opportunity are formed in the entrepreneurial process, which is characterized by entrepreneurial learning. During the entrepreneurial journey, the entrepreneur repeatedly reassesses the maturity of his business/venture idea and venture creation process to enter the market. The entrepreneur's decisions are influenced by both objective and affective circumstances. This study aims to identify and map the fluctuations of idea-opportunity perception and affection by a student entrepreneur throughout the entrepreneurial learning journey simulating a genuine entrepreneurial (learning) process. The data collection of variables took place during an entrepreneurship course that modeled the entrepreneurial journey via process-based entrepreneurship training and applying feasibility and attractiveness self-assessment, observation and in-depth interviews. A small group of doctoral students developed their business ideas during a process-based entrepreneurship course. After each lesson and homework, they assessed the feasibility and attractiveness of their idea and opportunity. The results showed asynchronous fluctuations in these individual context-based perception variables, frequently depending on the progression of the entrepreneurial journey. The study added the concept of affective artifact and some generalizing dimensions to describe the entrepreneurial journey. Recommendations are given for the implementation and research of entrepreneurial process-based training.
Keywords: 350; affect; attractiveness; entrepreneurial idea; entrepreneurial journey; entrepreneurial opportunity; feasibility; perception; perceptual fluctuation; process-based entrepreneurship training